슈퍼커패시터용 그래핀-산화아연 전극의 급속열처리에서 수소의 영향 - 정우준(Woo-Jun Jeong); 오예찬(Ye-Chan Oh); 김상호(Sang-Ho Kim) (Biuletyn Uniejowski, 2019)
With recent demand for the renewable energy resources, we conducted a research on the energy conversion and storage device of supercapacitor. The hybrid graphene-zinc oxide(GZO) electrodes for the supercapacitors (SCs) were fabricated and investigated. To increase the electrical conductivity of the GZO electrode, the rapid thermal annealing(RTA) in $Ar/H_2$(10%) atmosphere was applied and the effect was examined by comparing it with RTA at Ar atmosphere. In Raman spectroscopy, the electrodes annealed at 400? in $Ar/H_2$ atmosphere showed a lower ratio of D/G peak than that of annealed at Ar atmosphere, and had a larger specific capacitance(Sc) in the cyclic voltammetry(CV), and a lower the equivalent series resistance(ESR) in the electrochemical impedance spectroscopy(EIS). The reason seems to come from the better mixing of the graphene and zinc oxide by the RTA in $Ar/H_2$(10%).